COVID's Influence on Black Lives Matter: How Interest Convergence Explains the 2020 Call for Equality and What That Means for Administrative Racism. (3rd September 2022) - Heckler, Nuri; Mackey, Janiece
Abstract: This article argues that COVID created an interest convergence that led to the Black Lives Matter (BLM) rejuvenation in 2020. The critical race theory concept, interest convergence argues that the murder of George Floyd accelerated the BLM movement because of its overlap with the need for white U.S. to develop moral authority in the face of racism exposed by COVID. Gains created by interest convergence are ephemeral, and this article explores autoethnographic data of a Black-led nonprofit to test the proposition that interest divergence was almost instantaneous. Finding evidence of interest divergence, a model is developed for cultivating racial justice through cultural humility and a power realignment through interest cognizance.